GEOGRAPHICAL POSITION OF THE REPUBLIC OF UZBEKISTAN. ADMINISTRATIVE AND TERRITORIAL DESIGN OF THE REPUBLIC OF UZBEKISTAN. POPULATION AND CLIMATE - Teshaboyeva Nafisa Zubaydulla qizi,; Erkinova Muqaddas Olim qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ANNOTATION: The article examines the geographical position, administrative and  territorial  organization,  population  structure,  and  climatic  conditions  of  the Republic of Uzbekistan through an analytical and systematic approach. Emphasizing the  country’s  strategic  location  at  the  center  of  Central  Asia,  the  study  highlights Uzbekistan’s role as a crucial geopolitical and economic corridor connecting major regional markets. The research outlines the nation’s administrative framework, which includes the Republic of Karakalpakstan, twelve regions, and the capital city Tashkent, noting  its  significance  in  ensuring  effective  governance  and  regional  development. Furthermore, the article explores demographic trends characterized by a predominantly young population and rapid urbanization, which collectively influence socio-economic transformation. The analysis also addresses the country’s sharply continental climate, marked  by  extreme  temperature  variations,  scarce  precipitation,  and  high  solar radiation,  and  evaluates  its  implications  for  agriculture,  water  management,  and environmental  sustainability.  Overall,  the  annotation  underscores  the  multifaceted factors that shape Uzbekistan’s national development and geographic identity.